Reducing Phone Snubbing (Phubbing) Behavior Among The Young Generation Through The Islamic Education System - Kurniawan, Dandi; Widayanti, Rizka (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) IAIN Pontianak, 2023)
The phubbing phenomenon among the younger generation is currently in a very worrying phase. This phenomenon can be found anywhere and at any time, regardless of place and time. Phubbing, or phone snubbing, is a behavior change when interacting socially by ignoring the surrounding environment caused by excessive use of smartphones. The younger generation is the most vulnerable to contracting phubbing because of the emergence and spread of smartphone technology along with the birth of this generation. In response to this problem, the Islamic education system can be a solution to reducing that behavior. In this research, the author tries to explore the causes of phubbing behavior among the younger generation and what solutions the Islamic education system offers to overcome this problem. A qualitative technique and a descriptive research design are used in this study. This research’s data comes from observations of scientific journals and online articles related to the problems above. The research results are: 1) The phubbing phenomenon among the younger generation is caused by smartphone addiction. 2) The Islamic education system can be a solution to overcome these problems because it pays great attention to character education. 3) In its application, Islamic educators and those responsible for Islamic education must apply the education methods taught by the Islamic religion. The findings of this study will give a general picture of the risks of phubbing for the younger generation and serve as a reminder to every element of society of their responsibility for the character of the younger generation.